Effectiveness and costs of implementation strategies to reduce acid suppressive drug prescriptions: a systematic review - Hoes Arno W; Smeets Hugo M; de Wit Niek J (BMC, 2007)
Abstract Background Evaluation of evidence for the effectiveness of implementation strategies aimed at reducing prescriptions for the use of acid suppressive drugs (ASD). Methods A systematic review of intervention studies with a design according to research quality criteria and outcomes related to the effect of reduction of ASD medication retrieved from Medline, Embase and the Cochrane Library. Outcome measures were the strategy of intervention, quality of methodology and results of treatment to differences of ASD prescriptions and costs. Results The intervention varied from a single passive method to multiple active interactions with GPs. Reports of study quality had shortcomings on subjects of data-analysis. Not all outcomes were calculated but if so rction of prescriptions varied from 8% up to 40% and the cost effectiveness was in some cases negative and in others positive. Few studies demonstrated good effects from the interventions to reduce ASD. Conclusion Poor quality of some studies is limiting the evidence for effective interventions. Also it is difficult to compare cost-effectiveness between studies. However, RCT studies demonstrate that active interventions are required to reduce ASD volume. Larger multi-intervention studies are necessary to evaluate the most successful intervention instruments.